Occurrence of campylobacter in wild bird, and chickens and ducks in selected Malaysian farms - Mohamed, Mohamed Yousif Ibrahim (2014)
Poultry, in particular chickens and wild birds are reported to be frequently infected with Campylobacter. It is well recognized that Campylobacter jejuni is one of the main causes of gastroenteritis in humans, and poultry meat is reported to be the main source. A number of studies in the country had shown the occurrence of Campylobacter in chicken and chicken meat. Wild birds were observed in abundance at market places and farms. It was reported that wild birds may harbor and transmit Campylobacter to farm animals. However, very few studies had been carried out on Campylobacter in wild birds in Malaysia and the antibiotic resistance status of Campylobacter in these birds was not known. Thus, this study had three main objectives: the first objective was to determine the occurrence of Campylobacter in the wild birds in open environment away from poultry farms and those near poultry farms; secondly, to determine the prevalence of Campylobacter in poultry (chickens and ducks) in the farms and thirdly, to determine the antibiotic resistance patterns among Campylobacter isolates. The birds in open environment in five locations (>5 km away from poultry farms) (92) and near six poultry farms (66) were humanely trapped using mist net. The photograph of each bird was taken and the birds were given an identification mark; once the cloacal swab was taken, the birds were released. Six poultry farms were visited and cloacal swabs were taken from 101 chickens from three farms and 103 were taken from ducks in three duck farms. In the laboratory, the swabs were directly streaked onto selective agar media and incubated under microaerophilic condition for isolation of Campylobacter. Suspected colonies of Campylobacter were subjected to biochemical tests for phenotypic identification. The confirmation of the isolates was done using multiplex polymerase chain reaction (mPCR) assay. From 66 birds belonging to nine species trapped near the farms environment, 20% were positive for Campylobacter and out of these, 92.3% was C. jejuni. Eurasian Tree Sparrow (39.3%) followed by Rock Pigeon (34.8%) were frequently trapped. A total of 92 birds belonging to 12 species were caught in the open environment. The most frequent bird species identified positive to C. jejuni and C. coli was Eurasian Tree Sparrow (62%), followed by Rock Pigeon (25.8%). Twenty seven percent (27%) of the birds in open environment were found positive for Campylobacter and most of the isolates were identified as C. jejuni (60%). In the farms, a total of 40% of poultry were Campylobacter-positive; of these 29% of the ducks were positive for Campylobacter spp. of which 80% were C. jejuni, while 20% were C. coli. In chickens, a high prevalence of Campylobacter spp. was isolated at 60.3% and all 100% were C. jejuni. The Campylobacter isolates were subjected to antibiotic susceptibility test using disc diffusion method. The isolates were tested against 12 antibiotics, namely clindamycin, erythromycin, tetracycline, streptomycin, cefotaxime, ampicillin, gentamicin, nalidixic acid, enrofloxacin, ciprofloxacin, sulfamethoxazole-trimethoprim and chloramphenicol. The Campylobacter isolates from wild birds in open environment showed resistance to 2-9 antibiotics. The highest resistance was to cefotaxime and clindamycin (92.9% each), followed by nalidixic acid and streptomycin (78.6% each), tetracycline (64.3%) and chloramphenicol (57.1%). Those birds around poultry farms showed resistance to 1-4 antibiotics and the highest resistance was to clindamycin (66.7%) and less than 50% to the other four antibiotics. The isolates from poultry showed resistance to 1-9 antibiotics and highest resistance was to clindamycin (87.7%), followed by erythromycin (69.2%) and tetracycline (63.1%). From this study, it was found that Campylobacter was prevalent in wild birds in the open environment and near poultry farms and in chickens and ducks in the farms. The Campylobacter showed high resistance to antibiotics. Therefore, the birds could play a role in the dispersal and spread of antibiotic resistant Campylobacter in the environment and poultry farms. Thus, the presence of Campylobacter in wild birds, poultry and the environment may cause health hazard to human upon exposure to the organisms.